Decomposition of the organic matter in two forest ecosystems (Natural Park of Montseny, Spain) - I. Abundance, biomass and distribution of the soil microarthropods - Andres, P.; Athias-Binche, F. (VIE ET MILIEU-LIFE AND ENVIRONMENT, 1998)
This paper represents the first part of a larger work concerning the importance of the oribatid mites in the edaphic trophic chains of two forests (holm-oak and beech woods) under Mediterranean conditions. We offer here the data relating to annual changes of abundance, biomass and vertical distribution of the mesofauna sorted according taxonomic and trophic criteria. The soil was divided into three layers : fresh fallen leaves (L), fermentation layer (F) and organic horizon (S). Rate of leaf imput, dynamics of decomposition, environmental trophic supply, physical structure of the soil and seasonal drought constitute the factors determining the richness and the spatial arrangement of the fauna.
The following values have no corresponding Zotero field: pub-location: LABORATOIRE ARAGO, BP 44, 66651 BANYULS-SUR-MER CEDEX, FRANCE publisher: OBSERVATOIRE OCEANOLOGIQUE BANYULS
Keywords: decomposition; green oak woodlands; microarthropods; Soil

Decomposition of the organic matter in two forest ecosystems (Natural Park of Montseny, Spain) - I. Abundance, biomass and distribution of the soil microarthropods - Andres, P; Athias-Binche, F (VIE ET MILIEU-LIFE AND ENVIRONMENT, 1998)
This paper represents the first part of a larger work concerning the importance of the oribatid mites in the edaphic trophic chains of two forests (holm-oak and beech woods) under Mediterranean conditions. We offer here the data relating to annual changes of abundance, biomass and vertical distribution of the mesofauna sorted according taxonomic and trophic criteria. The soil was divided into three layers : fresh fallen leaves (L), fermentation layer (F) and organic horizon (S). Rate of leaf imput, dynamics of decomposition, environmental trophic supply, physical structure of the soil and seasonal drought constitute the factors determining the richness and the spatial arrangement of the fauna.
Keywords: decomposition; green oak woodlands; microarthropods; Soil